2015
DOI: 10.1089/dia.2013.0374
|View full text |Cite
|
Sign up to set email alerts
|

Skin Autofluorescence and Complications of Diabetes: Does Ethnic Background or Skin Color Matter?

Abstract: Skin AF measurement is a valuable tool for the assessment of micro- and macrovascular complication risk in patients with light skin color types. Even after exclusion of patients with too low a reflectance, the current performance of the AGE Reader™ (DiagnOptics Technologies BV, Groningen, The Netherlands) was insufficient in darker-skinned patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…The study was approved by the local ethical committee of the Slotervaart Hospital, Amsterdam, the Netherlands. A total of 126 patients from a larger, previously described 33 cohort of patients with type 2 diabetes were included in the study. The cohort was recruited between May 2009 and December 2010 and consisted of patients visiting the Department of Internal Medicine, Slotervaart Hospital, for their annual comprehensive diabetes evaluation.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was approved by the local ethical committee of the Slotervaart Hospital, Amsterdam, the Netherlands. A total of 126 patients from a larger, previously described 33 cohort of patients with type 2 diabetes were included in the study. The cohort was recruited between May 2009 and December 2010 and consisted of patients visiting the Department of Internal Medicine, Slotervaart Hospital, for their annual comprehensive diabetes evaluation.…”
Section: Patientsmentioning
confidence: 99%
“…In addition to UAE and glucose biochemistry, the patients were characterized in terms of plasma lipid profile and serum and urinary creatinine by standard biochemical assays, as described previously. 33 Both blood and urine samples were centrifuged at 2000 Â g to obtain EDTA plasma and urine supernatant, respectively. To characterize normal values for sTAM receptors in body fluids, plasma and urine were collected from 18 healthy volunteers (nonobese, without diabetes mellitus, metabolic syndrome, hypercholesterolemia, hypertension, cardiovascular, or renal disease, age >40 years).…”
Section: Patientsmentioning
confidence: 99%
“…Recently, more studies confirmed the positive association between SAF and one or more complications. Four (cross-sectional) studies showed an independent relation between SAF and both micro- and macrovascular complications in T2DM [ 52 55 ]. Ahdi et al .…”
Section: Micro - and Macrovascular Complications In Diabetesmentioning
confidence: 99%
“…Details on the measurement of blood pressure, the routine analysis of blood samples for fasting lipids, glucose, HbA1c, high-sensitivity Creactive protein (hs-CRP), and (micro)albuminuria, and the clinical definitions for diabetes-related microvascular (nephropathy, retinopathy, and neuropathy) and macrovascular complications are described elsewhere [17].…”
Section: Clinical Data Measurements and Definitionsmentioning
confidence: 99%